Mawson's remarkable men the personal stories of the epic 1911-14 Australasian Antarctic Expedition - Jensen, David C. (Allen and Unwin, 2015)
In 1911, the Australian Antarctic Expedition under Douglas Mawson left Hobart on the Aurora, headed for Antarctica. Much is known about Mawson and tales of his exploits are often retold. But Mawson did not go alone. What of the men who set off with him and without whom he could have achieved little? Who were they? Where did they come from? The 32 land-based members of the AAE of 1911-14 selected to explore part of the Antarctic continent where no person had set foot before, had an average age of just 26. They included three doctors, two soldiers, engineers, sailors, a Rhodes Scholar, a meteorologist, wireless operators, a photographer, a former 'female' spy, a lawyer-cum -mountaineer, an architectural draftsman and scientists. Just three had previously experienced the cold, loneliness, potential danger and isolation that only Antarctica offers. The remaining 29 could safely be described as enthusiastic novices; some had probably never before seen snow. Two of them were not to return, but all will remain part of the Antarctic's 'heroic era' of exploration